2011
DOI: 10.1002/ange.201006689
|View full text |Cite
|
Sign up to set email alerts
|

Eine verbesserte Synthese von Efavirenz durch asymmetrische Autokatalyse

Abstract: Ein Intermediat, das für sich selbst sorgt: Eine asymmetrische autokatalytische Zinkacetylid‐Addition benötigt katalytische Mengen des enantiomerenreinen Produkts als Teil einer Mischung chiraler Reagentien. Diese neue Strategie führt zu einer verbesserten Synthese einer wichtigen Efavirenz‐Vorstufe (siehe Schema).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 62 publications
(16 reference statements)
0
9
0
3
Order By: Relevance
“…In contrast, employment of ZntBu 2 resulted in a full conversion of dbz upon mixing of the substrates in toluene already at À20 8C (Scheme 1). This fast reaction led to the O-alkylated product [tBuZn- (1), which was isolated with high yield after a standard work up. The NMR data are fully consistent with the anticipated formula of 1 (see the Supporting Information), which was confirmed by X-ray crystallography (see below).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, employment of ZntBu 2 resulted in a full conversion of dbz upon mixing of the substrates in toluene already at À20 8C (Scheme 1). This fast reaction led to the O-alkylated product [tBuZn- (1), which was isolated with high yield after a standard work up. The NMR data are fully consistent with the anticipated formula of 1 (see the Supporting Information), which was confirmed by X-ray crystallography (see below).…”
Section: Resultsmentioning
confidence: 99%
“…To shed more light on the putative role of the zinc alkoxide product 2 in the observed course of the equimolar reaction, diffusion-ordered NMR spectroscopy (DOSY) investigations on the dibenzoyl/ZnEt 2 system were performed. 1 H DOSY measurements provide a reliable evidence of the approximate size of the species existing in solution. Very recently, it was demonstrated that the molecular weight of the species in question can be straightforwardly obtained by combining the Stokes-Einstein equation [Eq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations